Chinese Helicobacter pylori vaccine: Solution for an old challenge? - Talebi Bezmin Abadi, Amin (World J Gastrointest Pharmacol Ther, 2016)
Helicobacter pylori (H. pylori) is an important cause for gastric cancer in high risk individuals. H. pylori colonizes more than 50% of the world’s population and associated peptic ulcer disease and gastric malignancy have important public health implications. It has been classified as a class I carcinogen in 1994 by the World Health Organization. Clinicians are often prompted to eliminate the infection the moment it is detected. This also, unfortunately, led to reckless use of antibiotics and reports of increasing resistance are now worldwide. Each year, many of people die from gastric cancer; thus application of effective vaccine can reduce this relatively high mortality worldwide. H. pylori can be eliminated by antibiotics but efficacy is sharply decreasing. Moreover, current therapy is also expensive and with side effects. Vaccine may be the best solution to the above problem but there are many challenges in producing such an effective therapeutic vaccine. Recently, the Chinese group published in Lancet, a single-center, randomized, phase III study of an oral recombinant vaccine (Urease B subunit fused with heat-labile enterotoxin B derived from Escherichia coli) prescribed in the Chinese children (6-15 years) without a history of H. pylori infection. This review provides an insight into this new solution for an old challenge.